Analysis of The Carrying Capacity of Food Crop Follow-up As a Source of Ruminant Animal Feed In Kolaka Regency - La Ode Muh. Munadi; Muhammad Amrullah Pagala; Deki Zulkarnain; Muh. Obi Kasmin (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2021)
The research aims to analyze the ruminant and food crop integration system development in Kolaka Regency using LQ (Location Quotient) analysis and supporting capacity analysis, sourced from secondary data collected from various literature supporting this study. The analysis results showed that the base for cattle development is in Samaturu, Polinggona, and Watubangga subdistricts, and buffalo livestock development bases are located in Latambaga Wolo Iwoimendaa Subdistrict, Baula Subdistrict, Pomalaa Subdistrict, and Tanggetada Subdistrict. The base of goat livestock development is in latambaga, Iwoimendaa, Somalia, and Toari subdistricts with LQ1 values. As for the analysis of the carrying capacity of beef cattle feed, 19,724 heads (LU), buffalo 23,644 heads (LU), and goats 182,445 heads (LU). In conclusion, the utilization of food crop follow-up results can be a source of animal feed. It gives direction to the utilization of feed resources based on follow-up results.